Exchange rate and oil price interactions in selected CEE countries - Krzysztof Drachal (Economies, 2018)
This paper reports a study on the causal dynamics between spot oil price, exchange rates, and stock prices in Poland, the Czech Republic, Hungary, Romania, and Serbia. The results are compared with a benchmark analysis in which U.S. monthly data are used, and time periods are selected according to the flexibility of exchange rate regimes in each country. A period between 2000 and 2015 is analyzed. The methodology is based on the Granger causality test, and the non-linear Diks-Panchenko test, while the causality in variance is checked with the Hafner-Herwartz test.
Keywords: C32; C53; E37; F31; F37; G17; 330; causality; exchange rates; non-linear causality; oil price; stock prices; volatility spillover